2020
DOI: 10.1111/jop.13051
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid variant of squamous carcinoma in recurrent and second primary tumors of the oral cavity

Abstract: Background: Sarcomatoid variant of oral squamous cell carcinoma (OSCC) is aggressive tumors that frequently recur and metastasize. Our aim was to determine the survival outcomes and factors that predict its incidence in recurrent and second primary tumors (SPT). Methods: We retrospectively analyzed the records of SPT and recurrent OSCC cases with sarcomatoid differentiation. The overall survival (OS) and disease-free survival (DFS) were determined by the Kaplan-Meier method. Logistic regression was used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Primary CS should be differentiated from spindle cell carcinoma (SpCC) (or sarcomatoid carcinoma), which is composed of carcinoma and malignant spindle cells without mesenchymal components [ 7 , 15 , 30 , 31 ]. SpCC is a controversial type of epithelial carcinoma [ 32 ]. The characteristics of a true CS are intermixed with biphasic histologic components (pleomorphic epithelial and heterologous mesenchymal components) [ 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary CS should be differentiated from spindle cell carcinoma (SpCC) (or sarcomatoid carcinoma), which is composed of carcinoma and malignant spindle cells without mesenchymal components [ 7 , 15 , 30 , 31 ]. SpCC is a controversial type of epithelial carcinoma [ 32 ]. The characteristics of a true CS are intermixed with biphasic histologic components (pleomorphic epithelial and heterologous mesenchymal components) [ 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCSCC is an aggressive malignancy and tends to recur locally; however, the prognosis is similar to that of conventional SCC [ 4 ]. When SCSCC occurred as a second primary tumor in a different part of the oral cavity, it has more favorable clinical outcomes than those occurring as a recurrent tumor in the same site of the primary tumor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These codes were applied to large datasets, such as the SEER database, to predict the survival rate and chances of neoplasm patients. 5,6 The studies compared the performance of different codes and found that certain models, such as DT and SVM, achieved high accuracy in predicting the survivability of neoplasm patients. Ensemble methods combining multiple classifiers also showed promising results.…”
Section: Introductionmentioning
confidence: 99%